2016
DOI: 10.1093/labmed/lmw046
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2 Methods of Clot Solubility Testing in Detection of Factor XIII Deficiency: Table 1.

Abstract: The clot solubility test with 5M urea as solubilizing method and thrombin as clotting agent is more sensitive in the detection of FXIIID, but simultaneous use of the 2 methods can prevent misdiagnosis of a considerable number of patients with FXIIID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…[10][11][12][13][14][15] Although the diagnosis of FXIII deficiency in Iran is still performed mostly by means of clot solubility tests, using 1% monochloroacetic acid (MCA) and 5M urea, several newer and improved diagnostic techniques, including FXIII activity assays and molecular analysis are growing in use in recent years. It has been shown that clot-solubility tests cannot detect all patients with severe FXIII deficiency in southeastern Iran, 16,17 which is similar to experience seen elsewhere. 18 Although UCB is the leading clinical symptom leading to a diagnosis of FXIII deficiency, both in Iran and worldwide, ICH is the main cause of death in these patients.…”
Section: A Mini-review Of Prior Art In Relation To Factor XIII Deficisupporting
confidence: 77%
“…[10][11][12][13][14][15] Although the diagnosis of FXIII deficiency in Iran is still performed mostly by means of clot solubility tests, using 1% monochloroacetic acid (MCA) and 5M urea, several newer and improved diagnostic techniques, including FXIII activity assays and molecular analysis are growing in use in recent years. It has been shown that clot-solubility tests cannot detect all patients with severe FXIII deficiency in southeastern Iran, 16,17 which is similar to experience seen elsewhere. 18 Although UCB is the leading clinical symptom leading to a diagnosis of FXIII deficiency, both in Iran and worldwide, ICH is the main cause of death in these patients.…”
Section: A Mini-review Of Prior Art In Relation To Factor XIII Deficisupporting
confidence: 77%
“…The solubility method is a low‐cost test which may be used by laboratories where budgetary restraints are an issue . We have previously reported that sensitivity of the solubility screen can be improved by modification of reagents used to clot and lyse plasma , and subsequent studies have confirmed this finding ; however, in the second exercise, 7/12 PRO‐RBDD centres continued to use the least sensitive reagent combination, of calcium and urea.…”
Section: Discussionmentioning
confidence: 99%
“…A series of 2-fold dilutions of plasma was prepared with the dilution buffer (0.05 M imidazole, pH 7.4); then, a fibrinogen solution, kaolin suspension, thrombin-calcium mixture (human thrombin dissolved in 0.1 M calcium chloride) were added following the manufacturer's instructions. The mixture was incubated for 30 min at 37 • C, after which 5% monochloroacetic acid was added (to render unstabilized fibrin soluble) [36], and the mixture was incubated for another 5 min at 37 • C. After incubation, the tubes were shaken, centrifuged, and the absorption of soluble protein in the supernatant was measured at 280 nm using a Cary50 spectrophotometer (Varian, Palo Alto, CA, USA).…”
Section: Isopeptidase Assaymentioning
confidence: 99%